PENGARUH SOSIAL MEDIA, INFLUENCER, DAN ONLINE CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN PRODUK THE ORIGINOTE DI SHOPEE PADA MASYARAKAT KOTA KEDIRI - Nada Sari; Ahmad Jauhari; Edi Murdiyanto (Cahaya Ilmu Bangsa, 2025)
This research aims to determine the influence of social media, influencers, and online customer reviews on purchasing decisions for The Originote products on Shopee among the people of Kediri city. This research uses a type of quantitative research with an associative quantitative approach. This research produces: 1). The Social Media variable (X1) partially has a significant effect on the Purchasing Decision (Y) of The Originote Products at Shopee in the Kediri City Community with. 2). The Influencer variable (X2) partially has a significant effect on the Purchase Decision (Y) of The Originote Products on Shopee in the Kediri City Community 3). The Online Customer Review variable (X3) partially has a significant effect on the Purchasing Decision (Y) of The Originote Products on Shopee in the Kediri City Community 4). The variables Social Media (X1), Influencers (X2), and Online Customer Reviews (X3) simultaneously have a significant influence on the Purchasing Decision (Y) of The Originote Products on Shopee in the Kediri City Community.